Nicotine Replacement Therapy: A Clinical Approach - Anagha Shete; Mrinal Shete; Vaishnavi Lolage (New Visions in Medicine and Medical Science Vol. 6, 2024)
India’s diverse geography affects leading causes of death like TB, pulmonary, vascular, and neoplastic disorders. Smoking, a global issue, exacerbates poverty by diverting funds from essentials, while second-hand smoke poses health risks indoors. Second-hand smoke causes serious cardiovascular and respiratory diseases, including coronary heart disease and lung cancer, and kills around 1.3 million people prematurely every year [1]. China, Brazil and India are the largest tobacco leaf growers, with China accounting for 3.2 million metric tons [2]. The main tobacco farming practices in LMICs (low and middle-income countries) that are responsible for environmental degradation are the use of agrochemicals and deforestation to clear land for tobacco growing and for fuel wood used in the flue-curing of tobacco [3]. These practices lead to two major environmental consequences: ecosystem disruptions and soil degradation, which consequently lead to the loss of land resources, biodiversity and food insecurity [3]. Studies have shown that tobacco absorbs more nitrogen, phosphorus and potassium than other major food and cash crops, and therefore, tobacco growing decreases soil fertility more rapidly than other crops [4]. The addiction to tobacco and related products poses a great challenge to healthcare providers. Various forms of Nicotine replacement are available in the market. Each form is associated with a specific dosage, methods of usage and pros and cons. The selection of the modality for nicotine replacement depends upon multiple factors like type, duration and severity of addiction, affordability of the patient and availability of the product in the market. They can be used as a single modality or in combination with other products. The current chapter discusses various nicotine replacement therapies and their intricacies.